Karakteristik Ideal Semiprima Fuzzy - Abdurahim, Abdurahim; Anas, Andy Sofyan; Negara, Habib Ratu Perwira; Ahmad, Ahmad; Primajati, Gilang (Eigen Mathematics Journal, 2018)
A function  is called as an fuzzy prime ideal if every fuzzy ideal of  and  satisfies  caused  or  and a function  is called as an fuzzy semiprime ideal if every fuzzy ideal of  which requires  caused . The previous research has been studied the ideal characteristics of fuzzy prime. Since not all ideal fuzzy semiprime are ideal fuzzy prime, resulted in some characteristic of fuzzy semiprime ideal do not exist in characteristics of the fuzzy prime ideal. This study examines the characteristics of the fuzzy semiprime ideal along with some examples of those characteristics.